PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP RETURN ON EQUITY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017 - Kim Hek Tan; Elvie Maria; Sherry Christin (Universitas Methodist Indonesia, 2020)
This study aims to examine the effect of cash turnover, account receivable turnover, and inventory turnover on Return on Equity in Manufacturing Companies for the 2015-2017 period both partially and simultaneously. The data in this study are secondary data obtained from the Indonesia Stock Exchange website. While the research data sources are: Financial Reports of Manufacturing Companies in the consumer goods sector. The number of samples used was 22 companies taken from a population of 45 companies with the year observations of 5 years so the number of observations in this study was 66 observations. The analytical method technique used is multiple linear regression. The results showed that cash turnover and inventory turnover have a significant positive effect on Return on Equity while account receivable turnover has a significant negative effect on Return on Equity. Simultaneously cash turnover, account receivable turnover, and inventory turnover have a significant effect on Return on Equity in Manufacturing Companies.